A review on the bioactive, nutritional and medicinal properties of Zanthoxylum species and its effects on poultry productive performance and health - Olatunji, H.T.; Mohammed, A.E; Akande, K.E. (ADAN JOURNAL OF AGRICULTURE, 2026)
Plants are globally acknowledged as essential sources of food and medicinal treatments for various health conditions. The secondary metabolites produced by plants significantly influence both toxicity and health benefits. Zanthoxylum species are deciduous shrubs belonging to the Rutaceae family, comprise approximately 250 distinct species. This genus displays a wide array of biological functions due to its broad distribution and abundant bioactive compounds such as terpenoids, flavonoids, and alkaloids, enhancing its importance in medical applications as well as its insecticidal properties (larvicidal, repellent, and anti‑ feedant effects). Beyond therapeutic uses, Zanthoxylum species are commonly used as spices in various culinary traditions. In poultry production, Zanthoxylum supplementation has been associated with enhanced growth performance, improved immunity, and better overall well‑ being. The bioactive compounds, including antioxidants, alkaloids, and flavonoids, underline the therapeutic effects on growth and immunity. Additionally, antimicrobial and anti‑ inflammatory activities help maintain gut health and reduce the need for antibiotics, aligning with the growing trend toward natural and sustainable agriculture. This review critically examines the nutritional composition, bioactive phytochemicals, and documented effects of Zanthoxylum species on poultry growth performance, immune response, health and safety considerations.